MUSEUM AND CLINICAL STRAINS OF STREPTOCOCCI FOUND IN THE ORAL CAVITY AND THEIR SENSIBILITY TO A VARIETY OF ANTIBIOTICS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Streptococci strains of the anginous group isolated from various oral and maxillofacial infections were screened for their susceptibility to the following antimicrobial agents: benzylpenicillin, ampicillin, oxacillin, cephalothin, ceftazidime, cefotaxime, cefuroxime, erythromycin, clindamycin, tetracycline, chloramphenicol, vancomycin and trimethoprime-sulphamethoxazole. The isolates were susceptible to: clindamycin, chloramphenicol, vancomycin and all beta-lactam antibiotics, except ceftazidime to which 54.5% of the strains showed intermediate susceptibility. Intermediate susceptibility to tetracycline was found in 11.3% of the strains, whereas resistance to the same antibiotic was demonstrated in 61.4%. Resistance to erythromycin and trimethoprime-sulphamethoxazole was of 2.3% for both. In conclusion, penicillin is the drug of choice in infections caused by streptococci of the anginous group.